L’édition scientifique des documents comptables médiévaux : enjeux et perspectives d’une entreprise pluridisciplinaire - Aude Wirth-Jaillard (Perspectives Médiévales)
Medieval accounting documents are particularly interesting when it comes to the study of language (lexis, anthroponymy, punctuation, reported speech or syntax). Yet, as editors were not concerned with the linguistic representativity of a text, they often preferred literary texts over accounting documents. Nonetheless, accounts are of great interest for linguists, historians and archaeologists. Thus, it appears necessary to come up with editions of such documents according to a standard shared by all medievalists and based on the broad idea of faithfulness to the original text. Such electronic editions will consist in three layers – from the most faithful to the most normalized edition. The making of these editions and the treatment of their data will allow an effective interdisciplinarity.